2009
DOI: 10.1007/s12298-009-0038-2
|View full text |Cite
|
Sign up to set email alerts
|

Effects of 24-epibrassinolide and 28-homobrassinolide on the growth and antioxidant enzyme activities in the seedlings of Brassica juncea L.

Abstract: The present paper deals with the effects of two active forms of brassinosteroids (BRs) as epibrassinosteroid (24-EBL) and homobrassinosteroid (28-HBL) on percentage germination, growth in the form of shoot length, activities of auxinase (IAAO), polyphenol oxidase (PPO), superoxide dismutase (SOD), catalase (CAT) and ascorbate peroxidase (APOX) in 10 day old seedlings of Brassica juncea L. (RCM 619) under field conditions. Exogenous application of 240-EBL and 28-HBL significantly ameliorate the total protein co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
19
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(22 citation statements)
references
References 32 publications
3
19
0
Order By: Relevance
“…An increase in CAT activity after treatment with BR has also been reported earlier in rice [11], groundnut [37], Zea mays L. [10,38], tomato [39], Brassica juncea L. [40,41], and so forth. It may be inferred from the enhancement in CAT activity that BR application modulated the antioxidative metabolism resulting in better growth of plants as suggested earlier [42,43].…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…An increase in CAT activity after treatment with BR has also been reported earlier in rice [11], groundnut [37], Zea mays L. [10,38], tomato [39], Brassica juncea L. [40,41], and so forth. It may be inferred from the enhancement in CAT activity that BR application modulated the antioxidative metabolism resulting in better growth of plants as suggested earlier [42,43].…”
Section: Discussionsupporting
confidence: 76%
“…It may be inferred from the enhancement in CAT activity that BR application modulated the antioxidative metabolism resulting in better growth of plants as suggested earlier [42,43]. An increase in POX activity in response to the application of BRs has also been reported [40,41,44]. The POX has been implicated in the synthesis of lignin and other phenolic polymers.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…Brassinosteroids also enhances the crop productivity [6]. Brassinostroids being an eco-friendly chemical, has a potential application in agriculture to increase yield by regulating defense system under field condition in Brassica juncea L. Sirhindi et al [7]. Mitchell et al [8] reported about promotion in stem elongation and cell division by the treatment of organic extracts of rapeseed pollen.…”
Section: Introductionmentioning
confidence: 99%
“…BR stimulated somatic embryogenesis in cotton (Aydin et al 2006). BRs increased protein content and CAT and SOD activity in Brassica juncea L. under field conditions (Sirhindi et al 2009). However, HBL decreased protein content and SOD, catalase (EC 1.11.1.6) and peroxidase (EC 1.11.1.11) activities in germinating barley embryos (Kartal et al 2009).…”
Section: Discussionmentioning
confidence: 92%